Acting responsibly in the global marketplace: The relevance of Dietrich Bonhoeffer’s ethics for entrepreneurs in international value chains - van Tilburg, Aad (Stellenbosch Theological Journal, 2023)
In a value chain, products flow from primary producers to end users, often through intermediaries. The distribution of market power in each of the successive stages of the value chain is usually unequal and affects the financial compensation of participants. Unorganized primary producers in food or clothing chains tend to fall victim to heavy competition in consumer markets or to extreme efficiency requirements by retail chains. Increasingly, entrepreneurs running value chains are expected to take on responsibilities regarding the well-being of all participants, especially primary producers in developing countries. But what does acting responsibly mean for these entrepreneurs? Dietrich Bonhoeffer (1906–1945) provided clear guidance on what the content of acting responsibly should be for Christians and non-Christians alike. However, is his concept of acting responsibly also relevant for leaders in value chains? Entrepreneurs are expected to adopt corporate social responsibility (CSR) requirements, which, among other things, imply that all participants in a value chain enjoy an appropriate livelihood. I explore whether entrepreneurs, if they take Bonhoeffer’s criteria for responsible action seriously, do justice to all stakeholders in their value chain.